Ameliorative Effect of Taraxacum officinale Leaves on Hormonal Status of Hyperglycemic Rats (Indian Journal of Public Health Research & Development, 2021)
Acute or chronic side effects of hyperglycemia may affect all systems and organs, such as sexual glands.Approximately 90 percent of diabetic patients suffer from sexual dysfunction, including libido and fertility.This study is designed to investigate the effect of diabetes on the sex hormones levels ad to evaluate theameliorative effect of dandelion leaves powder (DLP) on diabetes-induced changes of gonadal hormonesand glucose serum levels in male rats. Experimental diabetes mellitus was induced by subcutaneous injectionwith 65mg streptozotocin STZ/kg body weight. DLP was given in pelleted food at ratio of 5% for 28 days.DLP was effective in lowering Follicle-stimulating hormone (FSH) serum level in dandelion-treated ratscompared to controls in diabetic group. DLP was also able to reverse the progesterone lowering effect ofdiabetes. In all of the classes, the estrogen level did not show any noticeable difference. It is suggested thatDLP can have a regulatory effect in male rats on diabetes-induced changes in gonadal hormone levels,especially progesterone. Our research has shown that long-term administration of DLP in the diabetesexperimental model could be used as a good candidate for reproductive hormone deficiency therapy
Keywords: Sex hormone - Dandelion (Taraxacum official) - Diabetes-Glucose - Rats.